Relación entre ansiedad, depresión, estrés y sobrecarga en cuidadores familiares de personas con demencia tipo alzheimer por mutación e280a en presenilina 1 (2010)
ABSTRACT: Cognitive and functional impairment of Alzheimer’s disease (AD) produces a significant impact on principal caregiver. Anxiety and Affective disorders are seen more often in relative caregivers of AD patients than in general population. Objective. To describe relationships among Anxiety, Depression, Stress and Overload in relative caregivers of people with Alzheimer type dementia presenilin-1 E280A mutation. Subjects and Methods. We selected 14 relative caregivers, to whom Anxiety, Depression, Stress and Overload scales were applied. For analysis, as scores of those scales were considered as caregiver’s variables such as age, gender, civil status, occupation, education, relationship, time of care and patient’s age. Results. Moderately high relations were found between Anxiety Trait and Depression(r=0,757; p=0,001), moderate between Anxiety State and Anxiety Trait (r=0,497; p=0,070), Depression(r=0, 451; p=0,105); moderate between Anxiety Trait and patient’s age (r=0,414; p=0,140), Stress (r=0,542; p=0,045), Overload (r=0,573; p=0,031), and moderately high with Depression (r=0,757; p=0,001); moderate between Depression and Overload (r=0,403; p=0,152); between Stress and Overload (r=493; p=0,072); between Overload and time of patient’s care (r=-0,523; p=0,054), Depression (r=0,403; p=0,152) and patient’s age (r=0,412; p=0,142). Conclusions. Three caregivers with increased stress levels were found, one with mild depression and other with intense overload and mild depression. None of participants presented increased Anxiety levels, but a trend to Anxiety Trait in patient’s offspring, allowing us to think in an individual character in these people.